Why Do We Do What We Do? Motivation in History and the Social Sciences - MacMullen, Ramsay (De Gruyter, 2014)
Why we do what we do is a matter of great interest to everyone, and everyone seems to have had their say about it - philosophers, sociologists, anthropologists, psychologists, economists, and historians perhaps the most, case by case. Occasionally the specialists have offered their ideas to a general readership, but mostly they prefer to speak to and with their fellows in their particular disciplines. To evaluate and compare their findings in a cross-disciplinary way is now for the first time attempted, by Ramsay MacMullen. Emeritus history professor from Yale University, he is the recipient of various academic awards, including a lifetime Award for Scholarly Distinction from the American Historical Association.